2021
DOI: 10.18060/24831
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of an Experimental Accelerometer for Assessing Countermovement Vertical Jump Height

Abstract: While force plate technology is the gold standard for assessment of many aspects of vertical jump performance, its cost is prohibitive to a broad spectrum of the population. Accelerometry may be more practical, inexpensive, and provide a simple solution that allows hands-on practitioners to readily assess vertical jump performance acutely and over time. Thus, the purpose of this study was to examine the accuracy of an experimental accelerometer for testing vertical jump heights derived from flight times when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The AB accelerometer placement significantly overestimated VJH during countermovement vertical jump with no arm swing, while no differences were observed for the remaining anatomical locations (CH, HP, and UB). Similar observations were made by Cabarkapa et al [16] who found that the accelerometer device placed 3 cm above the umbilicus (i.e., anterior abdomen) tended to overestimate VJH by approximately 3.1 cm during a countermovement vertical jump with no arm swing when compared to the force plate as a gold standard testing modality. The observed similarities may be attributed to researchers using the same accelerometer technology (StriveTech) for VJH assessment as well as similar anatomical placement (i.e., 5 cm vs. 3 cm inferior to the umbilicus).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The AB accelerometer placement significantly overestimated VJH during countermovement vertical jump with no arm swing, while no differences were observed for the remaining anatomical locations (CH, HP, and UB). Similar observations were made by Cabarkapa et al [16] who found that the accelerometer device placed 3 cm above the umbilicus (i.e., anterior abdomen) tended to overestimate VJH by approximately 3.1 cm during a countermovement vertical jump with no arm swing when compared to the force plate as a gold standard testing modality. The observed similarities may be attributed to researchers using the same accelerometer technology (StriveTech) for VJH assessment as well as similar anatomical placement (i.e., 5 cm vs. 3 cm inferior to the umbilicus).…”
Section: Discussionsupporting
confidence: 83%
“…Ground reaction force curves were computed from raw vertical acceleration data by adding acceleration due to gravity (9.81 m•s −2 ) and multiplying the resultant value with the subject's body mass, from which the following dependent variables were derived: peak concentric force (PCF; highest value observed during the concentric phase of the jumping motion), peak landing force (PLF; highest value observed during the landing phase of the jumping motion), and vertical jump height (VJH; i.e., calculated based on the flight time using the following equation [14,16]; (t 2 •g)/8; g = 9.81 m•s −2 , t = time in the air (sec)-determined as a change in the time between the first and last time point when the ground reaction force curve crosses zero value. The same dependent variables were obtained from the force plate system software (VALD, Force Decks Max, Brisbane, Australia).…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations